Homoeopathic Approach in Management of Rheumatoid Arthritis (Homoeopathy for All, 2021)
Arthritis is a general term. It literally refers to inflammation of joints. There are more than 100 types of arthritis. If we talk, the most common types of arthritis are osteoarthritis and rheumatoid arthritis. Rheumatoid Arthritis (RA) is one of the most common forms of chronic polyarticular inflammatory arthritis characterized by persistent synovial inflammation, bony erosions and progressive articular destruction leading to varying degrees of physical disability.1 It is characterized by periods of disease flares and remissions.2RA is a common chronic disease in developed countries.3 The prevalence of RA in adults women vary from 0.5 to 3.8 % and from 0.15 to 1.37% in men.4 The incidence of RA is at peak in the fourth decade of life.Incidence of arthritis were found higher in studies in people with low incomes and less education.5,6 These factors are particularly relevant for developing countries where many non-communicable diseases are rapidly encroaching upon the population.7Non- Steroidal Anti- Inflammatory Drugs (NSAIDs) are administrated to manage the RA in the conventional treatment. Gastric ulcers, bleeding and perforation are the most common known adverse reactions found associated with excessive consumption of NSAIDs. Homoeopathy is known to improve general wellbeing that act through immune system, many of these cases are referred to homoeopathy and successfully managed. In this article we have discussed about the rheumatoid arthritis and homoeopathic therapeutic for its management.
Keywords: Arthritis; management; conventional treatment